Peran Guru dalam pengembangan Kurikulum - Toni, Toni; Eliyanti, Endang Tri Siti; J. P. S., Togihon; Warneri, Warneri; Aunurrahman, Aunurrahman (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The curriculum in an education system is a very important component. The curriculum is also a dynamic teaching and learning vehicle so it needs to be assessed and developed continuously and continuously in accordance with existing developments in society. Teachers are tasked with carrying out the best teaching, so with that teachers are also responsible for implementing, fostering, and developing the school curriculum. Good teachers must be able to create good teaching and learning programs and assess and enrich the curriculum material that has been outlined.